Emerging technologies, opportunities and challenges for microgrid stability and control - Satapathy A.S.; Mohanty S.; Mohanty A.; Rajamony R.K.; M Soudagar M.E.; Khan T.M.Y.; Kalam M.A.; Ali M.M.; Bashir M.N. (Elsevier Ltd, 2025)
This work conducts an extensive survey that provides a complete overview of various control methodologies and stability considerations pertaining to Microgrids. Microgrids primarily function in a grid-connected manner, but they possess the capability to transition to standalone operation during emergency situations. Factors such as stability and operational control are of paramount importance in both modes of operation due to considerations such as frequency, voltage, optimal power transfer, and islanding detection, among others. The control topology and stability of microgrid applications and system modelling vary depending on the specific applications. This paper elucidates the stability considerations associated with remote and utility-based microgrids, encompassing various control and operation techniques pertaining to network characteristics. Various elements, including small-signal analysis, transient response, and voltage stability, have been proposed and their potential for enhancement has been examined. Following a concise examination of existing microgrid control approaches documented in the literature, the current study delves into an analysis of diverse methodologies for microgrid control and stability assessment. ? 2024 The Authors